Ancient cases of congenital disorders and their social causes - Pataricza, Dóra (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
More than 79 cases of children born with congenital defects are known from Greek and Roman literature. Although it is extremely difficult if not impossible to identify a single potential cause for it, attempts at explanation are already found in ancient writers. With the help of modern teratological science many teratogenous causes can partly be identified. Some of the most probable factors among these were the same as today: malnutrition, viruses, alcohol, vitamin deficiencies etc., but lead poisoning has to be taken also into account as a principal cause.